A gente vem brincar, colorir e até fazer atividade: a perspectiva das crianças sobre a experiência de frequentar uma instituição de educação infantil - Sandro Vinicius Sales dos Santos (2013)
This dissertation aims to examine the daily experiences of children aged four / five years within a public education. The study has a qualitative and interpretative character, and has been developed in a Municipal Unit of Child Education in the city of Belo Horizonte. From a multidisciplinary theoretical framework - which proposes a dialogue between authors (as) of childhood sociology and philosophy, expressed in the critical theory of Walter Benjamin and the pedagogies of childhood and kindergarten - built by the recognition of the specificities involving scientific research with children, we sought to understand the perspective of the same about their own education. The results of the study indicate that, for children, the institution of Child Education, in addition to the task of starting them in school life, is configured as a space of social relationships in early childhood. These relationships are much more extensive and complex than those experienced within the family. We also sought to understand the ways that children construct their experiences within the early childhood institution and, accordingly to that, it was identified that the experiences in UMEI articulate with extracurricular experiences of the children. Children also demonstrated ways of engaging with the actions planned by the teachers when such respect and embrace the playful dimension that involves the child's experience. Also, it was found that children like most of the situations, the moments, the activities and spaces where opportunity for higher level of ownership and involvement in actions, whether planned or unplanned by adults (those) who deal daily with the children in public contexts of care and education. From the analysis of the ways in which children construct their experiences in early childhood institution and identifying the experiences they most enjoyed, as well as those that did not like, it became possible to identify signs of children for the construction of pedagogical pratices more significant for then.